Enhancing metacognitive skills of students with different gender using simas eric learning model at state senior high school 6 Malang - Ericka Darmawan; Yuli Brasilita; Siti Zubaidah; Murni Saptasari (Universitas Negeri Jakarta, 2018)
The aim of the research is to know the influence of Simas eric (Skimming, Mind mapping, Questioning, Exploring, Writing, Communicating) cooperative learning model on difference gender on the XIth grade student’s metacognition skills of Biology in State Senior High School 6 Malang. This research was quasi-experimental with non-equivalent pretest posttest control group design. The sample used was XI MIA 1 and XI MIA 2 class of the State Senior High School 6 Malang. The data had been collected by observation of students’s metacognition skills. The data analysed by Anacova techniques showed that Simas eric learning model on difference gender effect on the XIth grade student’s metacognition skills in State Senior High School 6 Malang. The result of the research showed that Simas eric learning model influenced the XIth grade student’s metacognition skills, the difference gender and interaction of learning model and gender did not influence student’s metacognition skills.